Synthetic promoters for CHO cell engineering. Issue 8 (1st May 2014) - Brown, Adam J.; Sweeney, Bernie; Mainwaring, David O.; James, David C.
ABSTRACT We describe for the first time the creation of a library of 140 synthetic promoters specifically designed to regulate the expression of recombinant genes in CHO cells. Initially, 10 common viral promoter sequences known to be active in CHO cells were analyzed using bioinformatic sequence analysis programs to determine the identity and relative abundance of transcription factor regulatory elements (TFREs; or transcription factor binding sites) they contained. Based on this, 28 synthetic reporters were constructed that each harbored seven repeats of a discrete TFRE sequence upstream of a minimal CMV core promoter element and secreted alkaline phosphatase (SEAP) reporter gene. After evaluation of the relative activity of TFREs by transient expression in CHO‐S cells, we constructed a first generation library of 96 synthetic promoters derived from random ligation of six active TFREs inserted into the same reporter construct backbone. Comparison of the sequence and relative activity of first generation promoters revealed that individual TFRE blocks were either relatively abundant in active promoters (NFκB, E‐box), equally distributed across promoters of varying activity (C/EBPα, GC‐box) or relatively abundant in low activity promoters (E4F1, CRE). These data were utilized to create a second generation of 44 synthetic promoters based on random ligation of a fixed ratio of 4 TFREs (NFκB 5: E‐box 3: C/EBPα 1: GC‐box 1). Comparison of the sequence and relative activity of second generation promoters revealed that the most active promoters contained relatively high numbers of both NFκB and E‐box TFREs in approximately equal proportion, with a correspondingly low number of GC‐box and C/EBPα blocks. The most active second generation promoters achieved approximately twice the activity of a control construct harboring the human cytomegalovirus (CMV) promoter. Lastly, we evaluated the function of a subset of synthetic promoters exhibiting a broad range of activity in different CHO cell host cell lines (CHO‐S, CHO‐K1, and CHO‐DG44) and across extended fed‐batch transient expression in CHO‐S cells. In general, the different synthetic promoters both maintained their relative activity and the most active promoters consistently and significantly exceeded the activity of the CMV control promoter. For advanced cell engineering strategies our synthetic promoter libraries offer precise control of recombinant transcriptional activity in CHO cells spanning over two orders of magnitude. Biotechnol. Bioeng. 2014;111: 1638–1647. © 2014 Wiley Periodicals, Inc.